Audience Exposure to Broadcast Media Programme Messages on Insecurity in Plateau State, Nigeria - Blessed Adamu Nuhu; Tsegyu Santas; Anthony Ogande (Feedback International Journal of Communication, 2026)
Insecurity has become a major social and national concern in Nigeria, particularly in Plateau State. Broadcast media play an important role in disseminating information, shaping public awareness, and supporting efforts aimed at insecurity management. The study adopted a mixed methods research design, combining both quantitative and qualitative approaches. Quantitative data were collected through structured questionnaires administered to audiences of selected broadcast stations in Plateau State, while qualitative data were obtained through in-depth interviews with key informants and audience members. The quantitative data were analyzed using descriptive statistics such as frequencies and percentages, while the qualitative interview responses were analyzed thematically to complement and explain the survey findings. The findings revealed that straight news (42.5%) was the most commonly used programme format for communicating insecurity-related information, followed by discussion programmes (28.3%), analytical commentary (15.0%), and special reports (14.2%). However, audiences indicated a stronger preference for discussion-based programmes, as they offer deeper analysis and expert insights. The study also found that broadcast media messages largely emphasize government actions and security agency interventions, while less attention is given to community-based security initiatives. Audience exposure to insecurity-related broadcast messages was moderate, and the perceived effectiveness of these programmes in insecurity management was also moderate.